Endoscopically assisted craniosynostosis surgery (EACS): The craniofacial team Nijmegen experience. Issue 8 (August 2016) - Delye, Hans Hendrik Karel; Arts, Sebastian; Borstlap, Wilfred Ary; Blok, Laura Mirjam; Driessen, Jacques Jan; Meulstee, Jene Willem; Maal, Thomas Jan Jaap; van Lindert, Erik Jan
Abstract: Introduction: An evaluation of our first 111 consecutive cases of non-syndromic endoscopically assisted craniosynostosis surgery (EACS) followed by helmet therapy. Methods: Retrospective analysis of a prospective registration database was performed. Age, duration of surgery, length of hospital stay, blood loss, transfusion rate, cephalic index and duration of helmet therapy were evaluated. An online questionnaire was used to evaluate the burden of the helmet therapy for the child and parents. Results: 111 EAC procedures were performed: 64 for scaphocephaly, 34 for trigonocephaly and13 for anterior plagiocephaly. The mean age at the time of surgery was 3.9 (±1) months, mean surgical time was 58 (±18) minutes, mean blood loss was 34 (±28) ml, transfusion rate was 22% (n = 26), mean duration of postoperative helmet therapy was 10 (±2.5) months, mean preoperative and postoperative CI were respectively 0.67(±0.057) and 0.72 (±0.062) in scaphocephalic patients and the mean length of hospital stay was 2.6 (±1) days. The burden of the helmet therapy for the child and his family was deemed very low. Conclusion: EACS for non-syndromic patients shows low morbidity rates, short surgical time, short length of hospital stay, little blood loss and low need for blood transfusion and is associated with satisfying cosmetic results.